2014
DOI: 10.2527/jas.2013-7438
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior, ruminal fermentation, and performance of pregnant beef cows differing in phenotypic residual feed intake offered grass silage1

Abstract: This study examined the relationship of residual feed intake (RFI) and performance with feeding behavior and ruminal fermentation variables in pregnant beef cows offered a grass silage diet. Individual grass silage DMI (dry matter digestibility = 666 g/kg) was recorded on 47 gestating (mean gestation d 166, SD = 26 d) Simmental and Simmental × Holstein-Friesian beef cows for a period of 80 d. Cow BW, BCS, skeletal measurements, ultrasonically scanned muscle and fat depth, visual muscular score, ruminal ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 49 publications
8
42
0
1
Order By: Relevance
“…The more acidic rumen environment in the low-RFI lambs may be caused by the difference in feeding behavior. Though we did not measure the animal behavior in the current study, findings had been reported that low-RFI beef cattle chewed less (Kelly et al, 2010;Fitzsimons et al, 2014b), which means they are likely to produce less saliva to neutralize the acid in the rumen, which can result in the accumulation of acid in the rumen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The more acidic rumen environment in the low-RFI lambs may be caused by the difference in feeding behavior. Though we did not measure the animal behavior in the current study, findings had been reported that low-RFI beef cattle chewed less (Kelly et al, 2010;Fitzsimons et al, 2014b), which means they are likely to produce less saliva to neutralize the acid in the rumen, which can result in the accumulation of acid in the rumen.…”
Section: Discussionmentioning
confidence: 94%
“…Though in both of the studies cattle were offered grass silage, which is different from the diet in our study. However, Fitzsimons et al (2014b) reported that there was no difference in acetate to propionate ratio between the low-and high-RFI pregnant beef cows when they were fed a grass silage diet. In addition, no difference was observed in acetate to propionate ratio when the beef bulls were offered a high-concentrate diet (Fitzsimons et al, 2014c).…”
Section: Discussionmentioning
confidence: 98%
“…Fitzsimons et al (2014) found changes in backfat thickness, which were negative for low-RFI cows and positive for high-RFI cows. The reduction in backfat thickness in low-RFI cows suggested that these cows were mobilising more body fat to meet their nutritional requirements during pregnancy than high-RFI cows.…”
Section: Discussionmentioning
confidence: 88%
“…Currently, there are several reports arguing the interest, pertinence and possibilities of using RFI as a selection characteristic to increase feed efficiency and farm profitability in non-ruminants (Patience et al, 2015), but also in ruminants (beef: Fitzsimons et al, 2014; Gomes et al, 2012; dairy: Green et al, 2013; Potts et al, 2015; Pryce et al, 2014). There is a lack of information, however, in small ruminants, although some works have been developed mainly during the growth phase in sheep (Cockrum et al, 2013; Meyer et al, 2015; Redden et al, 2013) and the sheep industry has yet to fully investigate the potential impacts associated with selecting for RFI on carcass merit, growth traits, reproduction traits, and fleece characteristics (Cockrum et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation